Febre maculosa brasileira e outras rickettsioses no estado de Minas Gerais, 1995 a 2002 - Simone Berger Calic (2006)
Through a historical series of eight years (1995-2002), was analyzed in the data of the case report form (CRF) the positive cases of Brazilian Spotted Fever - BSF and other rickettsiosis for confirmation of clinical and epidemiological parameters consecrated in the literature. An exploratory study aimed st to interpret the information, objectifying the construction of the analysis of the epidemiological situation of the BSF in Minas Gerais. An analysis of the clinical symptoms of laboratory confirmed cases was carried through, in the same period, to verify the most prevalent, to improve the definition of a suspected case. A case-control study was carried through, using the (CRF) as intrument of risk factors identification.